Roles and performance enhancement of feed spacer in spiral wound membrane modules for water treatment: A 20-year review on research evolvement. (15th June 2021) - Lin, Weichen; Zhang, Yuting; Li, Danyang; Wang, Xiao-mao; Huang, Xia
Highlights: Evolvement of research on feed spacer in the past 20 years is divided into 3 phases. Research focus shifted from hydrodynamics via biofouling to novel spacer designs. Configuration of feed spacer has a crucial impact on hydrodynamics thence biofouling. Feed spacers were modified from the aspects of surface chemistry and geometry. Deeper understanding and optimization of the role of feed spacer are still in necessity. Abstract: Membrane technologies have been widely applied in water treatment, wastewater reclamation and seawater desalination. Feed spacer present in spiral wound membrane (SWM) modules plays a pivotal role in creating flow channels, promoting fluid mixing and enhancing mass transfer. However, it induces the increase of feed channel pressure (FCP) drop and localized stagnant zones that provokes membrane fouling. For the first time, we comprehensively review the research evolvement on feed spacer in SWM modules for water treatment over the last 20 years, to reveal the impacts of feed spacer on the hydrodynamics and biofouling in the spacer-filled channel, and to discuss the potential approaches and current limitations for the modification of feed spacer. The research process can be divided into three phases, with research focus shifting from hydrodynamics in Phase Ⅰ (the year of 2001–2008), to biofouling in Phase Ⅱ (the year of 2009–2015), and then to novel spacer designs in Phase Ⅲ (the year of 2016–2020). The spacer configuration has a momentous impact on the hydraulic performance regarding flow velocity field, shear stress, mass transfer and FCP drop. Biofouling initially occurs on feed spacer, especially around spacer filaments and the contact zones with membrane surface, and ultimately degrades the overall membrane performance indicating the importance of controlling spacer biofouling. The modification of feed spacer is mainly achieved by altering surface chemistry or introducing novel configurations. However, the stability of spacer coating and the economy and practicality of 3D-printed spacer remain a predicament to be tackled. Future studies are suggested to focus on the standardization of testing conditions for spacer evaluation, the effect of hydrodynamics on membrane fouling control, the design and fabrication of novel feed spacer adaptable for SWM modules, the application of feed spacer for drinking water production, organic fouling control in spacer-filled channel and the role of permeate spacer on membrane performance. Graphical abstract: Image, graphical abstract